Diversity in Grain, Flour, Amino Acid Composition, Protein Profiling, and Proportion of Total Flour Proteins of Different Wheat Cultivars of North India - Siddiqi, Raashid Ahmad; Singh, Tajendra Pal; Rani, Monika; Sogi, Dalbir Singh; Bhat, Mohd Akbar (Frontiers in Nutrition, 2020)
Wheat cultivars grown at three different locations of North- India were assessed for their variability in kernel and flour characteristics. Protein, wet and dry gluten contents of the flour varied significantly (p≤0.05) from 9.32-12.60 %, 23.46-43.04 %, and 8.28-15.00 % respectively. Wheat varieties exhibited moderate SDS-sedimentation and solvent retention values. Flour showed a significant (p≤0.05) difference in amino acid composition. Lysine having the lowest chemical score was the first most limiting amino acid in all wheat varieties. Variability of total flour proteins by SDS-PAGE showed polymorphism both in the number and intensity of bands particularly in the molecular weight range of 35.1-42.8 kDa corresponding to the α, β, and γ gliadin/LMW-GS region. Pearson correlation established between various grain and flour parameters showed a significant correlation which can result in better end product use.